Is N-methylacetazolamide a possible new therapy against ischemia-reperfusion injury? - Pardo, Alejandro Ciocci; Díaz Zegarra, Leandro A.; González Arbeláez, Luisa F.; Aiello, Ernesto A.; Mosca, Susana M. (Frontiers in Pharmacology, 2023)
The increase of intracellular Ca 2+ concentration, produced principally by its influx through the L-type Ca 2+ channels, is one of the major contributors to the ischemia-reperfusion injury. The inhibition of those channels in different experimental models was effective to ameliorate the post-ischemic damage. However, at a clinical level, the results were contradictory. Recent results of our group obtained in an ¨ex vivo¨ heart model demonstrated that a chemical derived from acetazolamide, the N-methylacetazolamide (NMA) protected the heart against ischemiareperfusion injury, diminishing the infarct size and improving the post-ischemic recovery of myocardial function and mitochondrial dynamic. A significant inhibitory action on L-type Ca 2+ channels was also detected after NMA treatment, suggesting this action as responsible for the beneficial effects on myocardium exerted by this compound. Although these results were promising, the effectiveness of NMA in the treatment of ischemic heart disease in humans as well as the advantages or disadvantages in comparison to the classic calcium antagonists needs to be investigated.